A serious laughing matter the intersection of gender and Filipino wit and humor as constructed in popular Philippine comedy television - Elumba, Maria Audrey Louise J. 1990-; Guieb, Eulalio R. III. (2012)
"Humor is an aspect of entertainment that we often take for granted. Indeed, it is unusual to be critical of something that seems inherently good--humor induces laughter, and yes we have heard of it over and over, 'laughter is the best medicine'. However, certain perspectives are emerging that put more focus on the negative aspect of humor. In his 2005 book, Laughter and Ridicule: a Critique of Humor, Michael Billig argues that humor plays a disciplinary role in shaping society by the way we behave. Simply put, he believes that the function of humor is that we behave in such a way that would not encourage others to make fun of us. What is worse is, we often point ridicule towards others, without conscientiously noticing the values and the ideologies that we gain from the comedy shows that we think we merely watch for amusement. What is it then that we find in Philippine comedy television nowadays? Treating women as sex objects is common in the Philippines, spanning decades of broadcast. Rimban said that this seemed trendy for an industry that heavily relies on mass-based programming where 'gory if not sexy video' had to go on air to nail high television ratings (as cited in Castro, 2009, p.2.). This is especially true for comedy shows such as sitcoms, though it has been hard to notice with the telenovelas and cheap sex films that keep most out attention towards such explicit sexual features. It is important to study humor because nobody intends to take it seriously, yet the ideas within it proliferate. It is even more important to study humor in the Philippine setting because not a lot have dared to. This study operates upon the following notions: (1) of humor as a form of discourse, and (2) gender as a system of meanings. Since comedic texts draw on prevalent ideologies, stereotypes, and cultural codes, analyses of humor offers a unique perspective for understanding contemporary perceptions and stereotypes of highly charged issues such as gender and sexuality (Billig, 2005; Boskin, 1997 as cited in Shifman & Dafna, 2010, p.1). This study also moves upon the assumption that television content --in this case powerful comedic texts -- has the strong ability to either affect or reflect society -- its norms, value system and conditions. It can shape ideas and beliefs, or merely portray it, in a more entertaining manner. Given this conceptual framework, this study aims to answer the following questions by doing an analysis of the most popular and certainly most enduring comedy shows in the country, Bubble Gang : (1) is there a Filipino type of humor that Filipinos subscribe to, evidently for years at a time, and what are the elements found within this type of humor? (2) Given gender as a set af meanings, what issues are found behind theses elements of humor? How prevalent and gender-specific issues within the text? (3) And lastly, what is the unique role of gender in the creation of these texts? What strategies does the show adopt to represent the realism of events and what kind of world does it construct? And to what extent are the representations in the show part of the struggle in the real world to either maintain or change power relationship across genders or sets of values and ideas? A qualitative approach will be use in this study through content analysis, though quantitative content analysis in a sense as well to measure the extent to which the humor used utilizes contain notions or issues of gender. Further research on contemporary gender studies will also be required to correlate the findings from the study through contextualization. The focus in interpreting the text will require the employment of formalist perspectives and methods as well, as frameworks particular to form will be formulated and utilized."
Vita.
Undergraduate thesis (A.B. Broadcast Communication)--University of the Philippines.
Keywords: Philippine wit and humor; Television comedies -- Philippines